Indicators of blood pressure according to the daily monitoring of elderly patients with paratraumatic eczema, concomitant varicose and hypertension - Ahmad Mohammadamin Ahmad Baninaser (Patologìâ)
Relevance. At the present stage varicose eczema incidence in the population is very common, but the data on mechanisms of paratraumatic eczema (varicose) with concurrent hypertension is not enough.